Accidental external rotation of distal interlock jig in retrograde femoral nailing can lead to more prominent screws. Issue 2 (February 2019) - Liu, Boshen; Comadoll, Shea M.; Hsu, Joseph R.; Matuszewski, Paul E.
Highlights: In retrograde femoral nailing, screws which appear flush with the medial cortex on AP imaging may be prominent. Accidental rotation of distal targeting jig in retrograde femoral nailing can increase the prominence of interlocking screws. The more distal an interlock is placed in retrograde femoral nailing, the more likely it is to be accidently prominent. Abstract: Objective: Symptomatic distal interlocking screws in retrograde femoral nailing are common due the difficulties of imaging the trapezoidal femur. Screws appearing to have appropriate length on imaging may possibly be prominent, creating symptoms. Screw trajectory may influence the degree of this radiographic error. We hypothesize that external rotation of screw trajectory will increase measurement error of screw length. Design: Retrospective. Setting: Urban Level I Tertiary Trauma Center. Participants: 283 patients with Computer Tomography (CT) scans of the native knee were retrospectively identified. Simulation was done of the trajectory of an interlock at 20 mm and 40 mm proximal to the nail entry point, which represent common screw positions associated/not associated respectively, with removal. The distance between the radiographic medial cortex and the tip of the transverse screw was calculated (D). The angle (Ψ) between the transverse trajectory and a modified trajectory aimed at the most medial cortex to avoid radiographic measurement error was calculated. Geometric modeling was utilized to calculate the measurement error (D) in the event of accidental external rotation. The angle of the medial slope was also measured (Θ). Intervention: Review of CT imaging of normal distal femora. Main Outcome Measurements: CT measurements of distal femora. Results: The mean distance (D) at 20/40 mm was 4.21 [95%CI 4.02–4.402] and 2.03 mm [95%CI 1.78–2.83], respectively (p < 0.0001). The mean angle (Ψ) between the transverse and modified trajectory at 20/40 mm was 12° [95%CI 11.5–12.5] and 9.60° [95%CI 9–10.2], respectively (p < 0.0001). External rotation by a similar amount nearly triples the measured difference (D). The measured medial slope was significantly increased as screws were placed more proximal (Θ20 mm 46.5 vs Θ40 mm : 48.7 °, p < 0.00001). Conclusion: The distance between the perceived medial cortex and the tip of the most transverse screw is 4.21 mm and could account for painfully prominent screws. In more proximal screws this distance is decreased. Internal rotation of the screw trajectory 12° can reduce this distance (D), which has implications in nail design. External rotation, amplifies this difference nearly three-fold. Surgeons should avoid external rotation of the aiming arm to prevent prominent screws.